Schur-Szegö composition of entire functions - Dimitrov, Dimitar Kolev [UNESP]; Kostov, Vladimir Petrov (My University, 2012)
For any pair of algebraic polynomials A(x) = n k=0 n k akxk and B(x) = n k=0 n k bkxk, their Schur-Szego composition is defined by ˝ (A ∗ n B)(x) = n k=0 n k akbkxk. Motivated by some recent results which show that every polynomial P(x) of degree n with P(−1) = 0 can be represented as Ka1 ∗ n ··· ∗ n Kan−1 with Ka := (x + 1)n−1(x + a), we introduce the notion of Schur-Szego composition of ˝ formal power series and study its properties in the case when the series represents an entire function. We also concentrate on the special case of composition of functions of the form exP(x), where P(x) is an algebraic polynomial and investigate its properties in detail.
Keywords: Schur-Szego composition; Entire functions; Hyperbolic polynomials; Laguerre-Pólya class